2014
DOI: 10.1103/physrevlett.112.215002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Reconnection and Intermittent Turbulence in the Solar Wind

Abstract: A statistical relationship between magnetic reconnection, current sheets, and intermittent turbulence in the solar wind is reported for the first time using in situ measurements from the Wind spacecraft at 1 AU. We identify intermittency as non-Gaussian fluctuations in increments of the magnetic field vector B that are spatially and temporally nonuniform. The reconnection events and current sheets are found to be concentrated in intervals of intermittent turbulence, identified using the partial variance of inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
121
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 68 publications
8
121
0
Order By: Relevance
“…Turbulence allows for the scale‐to‐scale transfer of fluctuation energy within a system. In many systems the direction of this energy transfer is from large to small scales and therefore turbulence can play a key role in driving the kinetic‐scale phenomena observed in space plasmas and dissipating large‐scale energy [ Matthaeus and Lamkin , ; Servidio et al , ; Donato et al , ; Wan et al , ; Stawarz et al , ; Osman et al , , , ; Kiyani et al , ]. While information about the small‐scale magnetic and electric field behavior has been well studied, for example, in the solar wind [e.g., Bale et al , ; Sahraoui et al , ], information about the kinetic‐scale velocity fluctuations (for both the ions and electrons) is more difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence allows for the scale‐to‐scale transfer of fluctuation energy within a system. In many systems the direction of this energy transfer is from large to small scales and therefore turbulence can play a key role in driving the kinetic‐scale phenomena observed in space plasmas and dissipating large‐scale energy [ Matthaeus and Lamkin , ; Servidio et al , ; Donato et al , ; Wan et al , ; Stawarz et al , ; Osman et al , , , ; Kiyani et al , ]. While information about the small‐scale magnetic and electric field behavior has been well studied, for example, in the solar wind [e.g., Bale et al , ; Sahraoui et al , ], information about the kinetic‐scale velocity fluctuations (for both the ions and electrons) is more difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…The intermittency may be anisotropic in nature. Osman et al [, ] showed that scaling behavior is non‐Gaussian and globally scale invariant when measuring along the local mean magnetic field, which is distinct from the classic multifractal scaling behavior seen when local mean magnetic field vector is transverse to the flow direction. The original solar wind turbulence with intermittency usually illustrates spectral anisotropies with an increase of the power‐law index from about −2 to about −1.5 when the sampling direction changes from longitudinal to transverse [ Horbury et al , ; Podesta , ; Wicks et al , ; He et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been utilized to identify these structures mostly as incremental changes in magnetic field from in-situ time-series data (e.g., Bruno et al 2001;Vasquez et al 2007;Borovsky 2008;Greco et al 2009a;Greco et al 2010;Miao et al 2011;Osman et al 2014;Greco et al 2016). However there generally lacks a synergy between the analyses of these two types of coherent structures, and the analysis method for the smallscale magnetic flux ropes is outdated.…”
Section: Introductionmentioning
confidence: 99%